EVALUATION OF TIGER SHRIMP (Penaeus monodon Fabr.) HATCHERY MANAGEMENT AT THE BRACKISHWATER AQUACULTURE DEVELOPMENT CENTER, JEPARA, CENTRAL JAVA - Dewi Nurhayati; Tuti Sumiati (Universitas Mataram, 2024)
The success of tiger shrimp production is influenced by the availability of quality postlarvae. The objective of this study was to evaluate biotechnical aspects of tiger shrimp hatcheries to produce quality postlarvae and analyse the economic aspects of tiger shrimp hatchery business in BBPBAP Jepara. The method used in this research was a case study method. Analysis of data used include analysis of biotechnical aspects of tiger shrimp hatchery maintenance and spawning broodstock, broodstock feed management, larval and post larvae rearing management, and water quality and health management. Analysis of economic aspects that include, cost analysis, revenue, income, and business feasibility analysis which includes, Payback Period (PP), and Net Present Value (NPV), Internal Rate of Return (IRR), Benefit Cost Ratio (B/C Ratio). The results showed that tiger shrimp broodstock tiger shrimp comes from nature, spawning using the ablation method, the feed used is fresh feed, the type of feed used, and the type of feed used. feed used in the form of fresh feed, the type of feed for larvae and tiger shrimp larval and post larvae consisted of phytoplankton, artemia, and artificial feed. The economic aspects analysed include business capital of IDR 1,063,000,000.00/year, fixed costs of IDR 216,300,000.00/year, production costs of IDR 368,670,000.00/year, income of IDR 960,000,000.00/year and profit IDR 375,030,000.00/year. The results of business feasibility analysis including the PP value of 1,9 years, PP (discount factor 6,16%) of 3,04 years, the NPV value of IDR 156,237,555.00, the B/C ratio of 1.64 and the IRR value 19.64%.